2022
DOI: 10.1007/s10811-022-02730-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Rhodomonas salina growth, biochemical composition, and taste, produced in semi-large scale under sunlight conditions

Abstract: Rhodomonas salina is a microalgal species, belonging to the cryptophytes, and is widely used as aquaculture feed because of its high nutritional profile and phycoerythrin content. This study investigated the effect of pH on the growth, biochemical composition, and taste of R. salina when cultivated on a semi-large scale under natural light conditions. Two tubular photobioreactors (200 L) were used for the cultivation of R. salina with sunlight as the only illumination source. Two different pH setpoints were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…1 and Table S3), it is plausible that once the alga became adapted to the higher pH during the lag phase, the growth resumed at the normal rate. In R. salina , a decrease in cell density has been observed at high (>10.5) pH levels ( 19 ), and recently, a growth inhibition at pH 8.5 compared to pH 7 has been demonstrated ( 48 ). In our experiment, however, the pH values never exceeded 8.5, which might explain the adaptation and compensatory growth resulting in no significant change in the AUC values.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Table S3), it is plausible that once the alga became adapted to the higher pH during the lag phase, the growth resumed at the normal rate. In R. salina , a decrease in cell density has been observed at high (>10.5) pH levels ( 19 ), and recently, a growth inhibition at pH 8.5 compared to pH 7 has been demonstrated ( 48 ). In our experiment, however, the pH values never exceeded 8.5, which might explain the adaptation and compensatory growth resulting in no significant change in the AUC values.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, at higher TCO 2 concentrations, the PC decreased, potentially due to insufficient nitrogen and carbon compounds. Latsos et al (2022) examined two distinct pH, namely 7 and 8.5 and observed that the PC reached its highest level (33.7%) at pH 8.5. In contrast, at pH 7, the PC was slightly lower (31.9%).…”
Section: Factors Influencing Protein Synthesis In Algaementioning
confidence: 99%
“…Latsos et al . (2022) examined two distinct pH, namely 7 and 8.5 and observed that the PC reached its highest level (33.7%) at pH 8.5. In contrast, at pH 7, the PC was slightly lower (31.9%).…”
Section: Factors Influencing Protein Synthesis In Algaementioning
confidence: 99%
“…A disadvantage of this non-concentrated storage approach is that large volumes of algae cultures must be stored. However, the pre-concentration of algae biomass (to 10-40 g OM/L) via low-shear technologies can offer a solution in this respect [10].…”
Section: Introductionmentioning
confidence: 99%